Smart health and innovation: facilitating health-related behaviour change. Issue 3 (31st August 2017) - Redfern, J.
Abstract : Non-communicable diseases (NCD) are the leading cause of death globally. Smart health technology and innovation is a potential strategy for increasing reach and for facilitating health behaviour change. Despite rapid growth in the availability and affordability of technology there remains a paucity of published and robust research in the area as it relates to health. The objective of the present paper is to review and provide a snapshot of a variety of contemporary examples of smart health strategies with a focus on evidence and research as it relates to prevention with a CVD management lens. In the present analysis, five examples will be discussed and they include a physician-directed strategy, consumer directed strategies, a public health approach and a screening strategy that utilises external hardware that connects to a smartphone. In conclusion, NCD have common risk factors and all have an association with nutrition and health. Smart health and innovation is evolving rapidly and may help with diagnosis, treatment and management. While on-going research, development and knowledge is needed, the growth of technology development and utilisation offers opportunities to reach more people and achieve better health outcomes at local, national and international levels.